Clarifying the identity of the Japanese Habu-kurage, Chironex yamaguchii, sp. nov. (Cnidaria: Cubozoa: Chirodropida) - Lewis, Cheryl; Bentlage, Bastian (Zootaxa, 2009)
Here we describe the new species Chironex yamaguchii (Cnidaria: Cubozoa) from the Ryukyu Archipelago, Japan. This highly venomous cubomedusa, commonly referred to as Habu-kurage in Japan, is the culprit for several fatalities in Japanese waters. The scientific name adopted for this species in the literature is Chiropsalmus quadrigatus, but our taxonomic investigations show that this represents a case of mistaken identity. In fact, Habu-kurage is a close relative of Chironex fleckeri, which is particularly interesting because the latter has a reputation for being the most venomous animal known. Differences in the shape of the pedalial canal bend, the number of tentacles, and bell size distinguish the two species. In addition to Japan, Chironex yamaguchii is widely distributed in the Philippines.